ROLE OF TAX MANAGEMENT OF SUBJECTS OF ECONOMIC ACTIVITY IN OPTIMIZATION OF THE ACTUAL ABILITY OF THE TAXPAYER TO PAYMENT OF INCOME TAX - Violetta Roschupkina (Вестник Северо-Кавказского федерального университета, 2022)
In the presented article research of the acts of the Russian Federation and Stavropol region granting the rightfor tax preferences on income tax of the organizations is conducted. Influence of tax preferences on the budget of the subject of federation is studied, influence on control and analytical work of tax authorities is calculated on replenishment of the budget of Stavropol region regarding collecting income tax of the organizations. Efficiency of tax planning in subjects of managing from the point of view of the depreciation policy elected by financial service of the organization is considered.